The influence of job burnout on the attention ability of army soldiers and officers: Evidence from ERP - Wu, Lin; Chen, Yanfeng; Liu, Xufeng; Fang, Peng; Feng, Tingwei; Sun, Kewei; Ren, Lei; Liang, Wei; Lu, Huijie; Lin, Xinxin; Li, Yijun; Wang, Lingling; et al. (Frontiers in Neuroscience, 2022)
Job burnout is one of the most widespread mental problems in today’s society and seriously affects the mental health and combat effectiveness of soldiers and officers. Herein, the effect of burnout on individual attention is studied from the perspective of neuroelectrophysiology. A total of 1,155 army soldiers and officers were included in this investigation and completed the Job Burnout Scale for Military Personnel. A total of 42 soldiers and officers were randomly selected from those with and without burnout to participate in an event-related potential (ERP) study using a visual oddball task. The characteristics of visual P3a and P3b at Fz, FCz, Cz, CPz, and Pz were recorded and analyzed by repeated-measures analysis of variance (ANOVA). P < 0.05 was the criterion for a significant difference. The total average score on the Job Burnout Scale for Military Personnel among the participants was 0.74 ± 0.46, and the detection rate of job burnout was 29.85%. In the Oddball task, the average number of target stimuli counted in the burnout group was lower than that in the control group, but no significant difference was found. For P3a, the Fz, FCz, Cz, CPz, and Pz amplitudes in the burnout group were significantly lower than those in the control group. The average amplitude of P3a evoked in the central parietal area was larger than that in the prefrontal area. For P3b, the amplitudes of the five electrodes in the burnout group were significantly lower than those in the control group. The average amplitude of P3b evoked in the parietal region was larger than those in the prefrontal and central parietal regions. A certain degree of job burnout is evident in army soldiers and officers. The voluntary attention and involuntary attention of individuals with burnout are both affected to some extent, as reflected by the lower amplitudes of P3a and P3b. The results suggest that P3a and P3b can be used as indicators to monitor cognitive neural function in soldiers and officers with burnout and can also be used as references for evaluating the effects of cognitive training and screening methods. In this study, ERP was used to research the attention ability of soldiers and officers with job burnout, and related issues were discussed from the aspects of the burnout results, behavioral results, ERP results, compensation effect of cognitive resources, application in the military field, limitations, and prospects.